Microstructural and nonlinear properties of Zn-V-Mn-Nb-O varistor ceramics with Gd2O3 substitution for low voltage application - Isa, Nor Hasanah; Zakaria, Azmi; Azis, Ra'ba'ah Syahidah; Rizwan, Zahid (Trans Tech Publications, 2017)
The effect of Gd2O3 substitution on the microstructural and electrical properties of Zn-V-Mn-Nb-O varistor ceramics sintered at 900°C was investigated. XRD, SEM, and EDAX results show that the GdMnO3 and GdVO4 phases formed at the grain boundaries and triple point junctions. Gd2O3 substitution inhibited the grain growth from 3.85 to 3.06 μm and increased the sintered ceramics density from 5.12 to 5.19 g/cm3. The samples containing the amount of 0.03 mol% Gd2O3 exhibit an optimum nonlinear coefficient α value which is 9.91, highest breakdown electrical field which is 88.48 V/mm and lowest leakage current density which is 0.11 mA/cm2 in low voltage application.